PROSES DAN PENDEKATAN REGENERASI PETANI MELALUI MULTISTRATEGI DI INDONESIA / Process and Approach to Farmer Regeneration Through Multi-strategy in Indonesia - Oeng Anwarudin; Sumardjo Sumardjo; Arif Satria; Anna Fatchiya (Badan Penelitian dan Pengembangan Pertanian, 2020)
The low share of young farmers in Indonesia must be a serious concern of the government in the future agricultural development program. The results of the agricultural census in 2013 showed that the portion of young farmers (<35 years) was 12.87%, far lower than the middle age (35-54 years) 54.37%, and the elderly (> 54 years) 32.76%. This situation encourages the importance of finding solutions to realize farmers’ regeneration. This paper describes the regeneration of farmers (processes, approaches, and strategies) through increasing the role of families, agricultural extension, community, agricultural modernization, and farmer corporations. Regeneration has the same terms as the succession and inheritance of agricultural business, which is the process of presenting new actors in agricultural business. Farmer regeneration can be in the family environment which means that the management of agricultural businesses is inherited from parents to their children, and non-family regeneration, namely inheritance of agricultural businesses, is shifted to newcomers who have no family relations. The regeneration process can be planned that is driven by outsiders and without a plan that is driven by the community itself. Approaches and strategies for farmers’ regeneration processes can be through strengthening the role of families, agricultural extension, community, agricultural modernization, and farmer corporations. The role of the family can be increased through the cultivation of respect, socialization, and inheritance of agricultural businesses. The role of agricultural extension workers as facilitators, communicators, motivators, consultants, and institutional development of young farmers can be strengthened. The role of the community through outreach, information transfer, and consultation can be intensified. Modernization of agriculture can be through the application of agricultural mechanization technology and smart farming or digital farming. Farmer corporations can be developed to attract the interest of the younger generation because they open opportunities for the availability of economically viable land, based on the specialization of expertise, the use of agricultural machinery, and improving the bargaining position of farmers.Keywords: Farmers, regeneration, corporation, agriculture, modernization AbstrakPorsi petani muda yang rendah di Indonesia harus menjadi perhatian serius pemerintah dalam program pembangunan pertanian ke depan. Hasil sensus pertanian tahun 2013 menunjukkan porsi petani muda (<35 tahun) 12,87%, jauh lebih rendah dibanding usia menengah (35-54 tahun) 54,37% dan usia lanjut (>54 tahun) 32,76%. Keadaan ini mendorong pentingnya mencari solusi mewujudkan regenersi petani. Tulisan ini memaparkan regenerasi petani (proses, pendekatan dan strategi) melalui peningkatan peran keluarga, penyuluhan pertanian, komunitas, modernisasi pertanian, dan korporasi petani. Regenerasi memiliki istilah yang sama dengan suksesi dan pewarisan usaha pertanian, yaitu proses menghadirkan pelaku baru dalam usaha pertanian. Regenerasi petani dapat di lingkungan keluarga yang berarti pengelolaan usaha pertanian diwariskan dari orang tua kepada anaknya, dan regenerasi nonkeluarga yaitu pewarisan usaha pertanian beralih kepada pendatang baru yang tidak memiliki hubungan keluarga. Proses regenerasi dapat terencana yang digerakkan pihak luar dan tanpa rencana yang digerakkan masyarakat sendiri. Pendekatan dan strategi proses regenerasi petani dapat melalui penguatan peran keluarga, penyuluhan pertanian, komunitas, modernisasi pertanian, dan korporasi petani. Peranan keluarga dapat ditingkatkan melalui penanaman sikap respek, sosialisasi, dan pewarisan usaha pertanian. Peranan penyuluh pertanian sebagai fasilitator, komunikator, motivator, konsultan, dan penumbuhkembangan kelembagaan petani muda dapat dikuatkan. Peranan komunitas melalui sosialisasi, transfer informasi, dan konsultasi dapat diintensifkan. Modernisasi pertanian dapat melalui penerapan teknologi mekanisasi pertanian dan smart farming atau digital farming. Korporasi petani dapat dikembangkan sebagai penarik minat generasi muda karena membuka peluang tersedianya lahan yang layak secara ekonomi, berbasis spesialisasi keahlian, penggunaan alat-mesin pertanian dan meningkatkan posisi tawar petani.Kata kunci: Petani, regenerasi, korporasi, pertanian, modernisasi